2008
DOI: 10.3144/expresspolymlett.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acetylation on properties of flax fibre and its polypropylene composites

Abstract: Abstract. Flax fibre was modified with acetylation. The influence of the acetylation on the structure and properties of flax fibre were investigated as well as modified flax fibre reinforced polypropylene composites were also prepared. The catalyst was used to accelerate acetylation reaction rate. Flax fibre was characterised after modification. Surface morphology, moisture absorption property, components content, degree of polymerisation, crystallinity of cellulose and thermal stability of flax fibres were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
254
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(264 citation statements)
references
References 19 publications
8
254
1
1
Order By: Relevance
“…Moreover, the decrease in the polarity of jute on acetylation can cause a reduction in its hydrophobicity. It is clear that, even though there was no direct chemical bond binding acetylated jute fabric and PLA, the increased hydrophobicity of jute after treatment is responsible for the improvement in its mechanical properties (Bledzki et al 2008). Table 3 shows the effect of KMnO4 treatment on the mechanical properties of treated jute fabric/PLA composites at 10 wt.% fabric loading.…”
Section: Mechanical Properties Of the Compositesmentioning
confidence: 99%
“…Moreover, the decrease in the polarity of jute on acetylation can cause a reduction in its hydrophobicity. It is clear that, even though there was no direct chemical bond binding acetylated jute fabric and PLA, the increased hydrophobicity of jute after treatment is responsible for the improvement in its mechanical properties (Bledzki et al 2008). Table 3 shows the effect of KMnO4 treatment on the mechanical properties of treated jute fabric/PLA composites at 10 wt.% fabric loading.…”
Section: Mechanical Properties Of the Compositesmentioning
confidence: 99%
“…Several studies have reported the improvement in mechanical properties of natural-fibre composites through alkali [14,15], acetyl [16] and silane [17,18] treatment of plant fibres. The chemical treatments react with the hydroxyl groups and improve the hydrophobic characteristics of fibres [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm and coconut trees contain many fibres, but coir fibre (CCF) from coconut, empty fruit bunch (EFB) and palm kernel (PKF) from oil palm belong to the class of fruit fibres. The major chemical compositions in these fibres are pectin, hemicelluloses, lignin and cellulose (Bledzki et al 2008). Natural fibre's compositions may vary with nature of the plant, geographical location, growing condition and chemical determination methods.…”
Section: Introductionmentioning
confidence: 99%
“…These natural fibres' limitation can be minimized through surface treatment, by using either chemical compatibilisers/coupling agents, grafting of polymer matrix or chemical modification agents on the lignocellulosic fibres (Khalil et al 2001). These surface treatments have significant effect on chemical compositions of the natural fibre, which in-turn leads to reduction in hydrophilic nature of the fibre and improvement in dimensional stability, interfacial adhesion and environmental degradation of the natural fibre (Bledzki et al 2008). In the present research work, the effect of the mercerization, alkaline bleaching and acetylation on empty fruit bunch (EFB), palm kernel (PKF) and coir fibres' (CCF) chemical compositions was investigated.…”
Section: Introductionmentioning
confidence: 99%